Screening and characterisation of lactic acid bacteria and substrates for lysine production - Toe, Cui Jin (2017)
Every year, large scale of amino acids (AA) production is required to meet the high demand in various industries especially the livestock industry. Most of the AA are produced from genetically engineered Corynebacterium glutamicum and Escherichia coli. However, there are increasing concern regarding the use of genetically modified microorganisms and products derived from these microorganisms which may have negative impact on human and environment. Therefore, it has urged the search for a safer food-grade producer strain. Previous studies reported that lactic acid bacteria (LAB) have the capability of producing AA owing to their well-established proteolytic system. However, the production of AA by LAB has not been studied extensively. Therefore, this study was conducted to establish the process of producing AA by selected LAB isolates using locally available substrates. Initially, phenotypic and genotypic characteristics of the selected LAB isolates were determined for the identification of LAB isolates. The results showed that all studied LAB isolates were stained Gram positive with seven LAB isolates were identified as Pediococci sp. and one Lactobacillus sp. The growth profile of all LAB isolates showed that active cultures were obtained at 10 h of incubation. Furthermore, a standard reference of Log colony forming unit (CFU)/mL versus optical density at 600 nm (OD600nm) was constructed to quantify the cell concentration for each LAB isolate. Subsequently, the detection of active extracellular proteolytic activity towards skim milk and azocasein under three different pH conditions showed that the extracellular proteolytic enzymes produced by LAB isolates were versatile and active over a broad pH range. The AA production profile of the eight LAB that were previously isolated from fermented tapioca were determined in MRS medium. Results showed that all LAB isolates were able to produce free isoleucine, glutamate, proline and glycine. The production of AA by LAB isolate was strains specific. Among the studied LAB isolates, the best amino acid producer was Pediococcus pentosaceus I-UP2 with a total of 15 different amino acids being produced. Moreover, P. pentosaceus I-UP2 also showed the most promising result for lysine production as compared to other LAB isolates. The increment of lysine production by P. pentosaceus I-UP2 was suggested to be attributed to the biodegradation mechanism, whereby the increment of proteolytic activity at pH 5 was also detected correspondingly. Hence, the increment of lysine content was most probably due to the enhancement of extracellular proteolytic activity released by P. pentosaceus I-UP2. Proximate analysis and AA determination on different substrates for lysine production was carried out prior to the selection of suitable substrates for factorial design. The results suggested that yeast extract, meat extract, peptone from casein, fish meal, mushroom waste, and fresh PKC were potential substrate for the production of lysine due to the availability of lysine and aspartate in these substrates. Based on the ANOVA results of 2-level fractional factorial design, meat extract, peptone from casein, mushroom waste and fresh PKC were revealed to be significant variables affecting the production of lysine by P. pentosaceus I-UP2. Validation of the identified variables showed that media V (meat extract, 8.18 g/L; peptone from casein, 7.41 g/L; mushroom waste, 57.87 g/L; glucose, 20 g/L; dipotassium hydrogen phosphate, 2 g/L; Tween 80, 1 mL; diammonium hydrogen citrate, 2 g/L; sodium acetate, 5g/L; magnesium sulphate heptahydrate, 0.2 g/L; manganases sulphate tetrahydrate, 0.04 g/L) was the best medium combination where up to 122% enhancement of lysine yield (54.75 mg/L) was detected. The present study will provide useful information to allow further attempts to explore the potential of LAB to produce AA and reduce the importation bill of Malaysia.